Answer:
21
Step-by-step explanation:
I did the math.
Step-by-step explanation:
C. y= -5x + 27
D. y=2x - 15
thats all
Answer:
C. If the radius decreases, then the height must decrease
Answer:
Step-by-step explanation:
Comment
Expand the second and 3rd factors first. Then worry about the x.
Solution
x(x + 2)(x + 4)
<em>first</em>: x * x = x^2
<em>Outside</em>: 4*x = 4x
<em>Inside</em>: 2*x = 2x
<em>Last:</em> 2*4 = 8
Combine
x^2 + 4x + 2x + 8
x^2 + 6x + 8
Now is the time to worry about the extra x
x(x^2 + 6x + 8)
remove the brackets.
x*x^2 + x*6x + 8*x
Combine
Answer: x^3 + 6x^2 + 8x
Answer:
No because if 2x+1=3x+3=6x how is that 0 so no
Step-by-step explanation: